2022
DOI: 10.3390/cryst12030407
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Slag

Abstract: The Special Issue on “Metallurgical Slag” is a collection of 23 original articles dedicated to theoretical and experimental research works providing new insights and practical findings in the field of metallurgical slag-related topics [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results of the analysis of hydraulic activity of the obtained slag granules showed that on average their activity on CaO absorption is 650-750 mg/g, which is almost twice higher than that of slag granulated by traditional water technologies [21,30,31]. The slag granulated in this way, in addition to its use in the production of construction and ceramic materials [32], can also be successfully used as a substitute for mineral abrasives applied for sandblasting of parts for various purposes [33].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The results of the analysis of hydraulic activity of the obtained slag granules showed that on average their activity on CaO absorption is 650-750 mg/g, which is almost twice higher than that of slag granulated by traditional water technologies [21,30,31]. The slag granulated in this way, in addition to its use in the production of construction and ceramic materials [32], can also be successfully used as a substitute for mineral abrasives applied for sandblasting of parts for various purposes [33].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Metallurgical slag is a byproduct generated during high-temperature metallurgical processes, and its large quantity and complex chemistry have been a burden and barrier to industrial development [10]. As a byproduct of iron ore, approximately 2.5-3 tons of iron tailings are generated for every ton of iron produced [11][12][13].…”
Section: Introductionmentioning
confidence: 99%